The Histone Deacetylase Inhibitor Suberoylanilide Hydroxamic Acid Alleviates Salinity Stress in Cassava - Patanun, Onsaya; Ueda, Minoru; Itouga, Misao; Kato, Yukari; Utsumi, Yoshinori; Matsui, Akihiro; Tanaka, Maho; Utsumi, Chikako; Sakakibara, Hitoshi; Yoshida, Minoru; Narangajavana, Jarunya; Seki, Motoaki (Frontiers in Plant Science, 2017)
Cassava (Manihot esculenta Crantz) demand has been rising because of its various applications. High salinity stress is a major environmental factor that interferes with normal plant growth and limits crop productivity. As well as genetic engineering to enhance stress tolerance, the use of small molecules is considered an alternative methodology to modify plants with desired traits. The effectiveness of histone deacetylase (HDAC) inhibitors for increasing tolerance to salinity stress has recently been reported. Here we use the HDAC inhibitor, suberoylanilide hydroxamic acid (SAHA), to enhance tolerance to high salinity in cassava. Immunoblotting analysis reveals that SAHA treatment induces strong hyper-acetylation of histones H3 and H4 in roots, suggesting that SAHA functions as the HDAC inhibitor in cassava. Consistent with increased tolerance to salt stress under SAHA treatment, reduced Na+ content and increased K+/Na+ ratio were detected in SAHA-treated plants. Transcriptome analysis to discover mechanisms underlying salinity stress tolerance mediated through SAHA treatment reveals that SAHA enhances the expression of 421 genes in roots, and 745 genes at 2 h and 268 genes at 24 h. The mRNA expression of genes, involved in phytohormone (abscisic acid (ABA), jasmonic acid (JA), ethylene, and gibberellin) biosynthesis pathways, is up-regulated after high salinity treatment in SAHA-pretreated roots. Among them, an allene oxide cyclase (MeAOC4) involved in a crucial step of JA biosynthesis is strongly up-regulated by SAHA treatment under salinity stress conditions, implying that salinity tolerance of SAHA-treated cassava is mediated through the JA pathway. Our results demonstrate that the application of the HDAC inhibitor allows cassava to improve tolerance to high salinity.